Mild Traumatic Brain Injury and Executive Functions in School-Aged Children - Maillard-Wermelinger, Anne (2009)
OBJECTIVE: This study sought to examine the effects of mild traumatic brain injury (TBI) on executive functions in school-aged children. PARTICIPANTS AND METHOD: The prospective, longitudinal study involved 8–15 year old children, 186 with mild TBI and 99 with mild orthopedic injuries (OI). They were administered the Stockings of Cambridge and Spatial Working Memory subtests from the Cambridge Neuropsychological Testing Automated Battery (CANTAB) about 10 days, 3 months, and 12 months post-injury. Parents completed the Behavior Rating Inventory of Executive Functions (BRIEF) on each occasion, with ratings at the initial assessment intended to assess premorbid functioning retrospectively. RESULTS: On the CANTAB, the groups did not differ on the Stockings of Cambridge, and the mild TBI group unexpectedly performed better than the OI group on Spatial Working Memory. On the BRIEF, children with mild TBI showed a marginally significant trend toward more problems than the OI group on the Metacognition Index composite. The only BRIEF subscale on which they demonstrated significantly more problems was Organization of Materials. The presence of intracranial abnormalities on MRI was associated with more problems on the BRIEF Organization of Materials subscale at 3 months, but other findings were not consistent with hypothesized effects of TBI severity. The CANTAB subtests were significant predictors of later ratings on the BRIEF, but accounted for modest variance. DISCUSSION: Children with mild TBI show limited evidence of deficits in executive functions, either cognitively or behaviorally, irrespective of injury characteristics. Cognitive tests of executive functions are modest predictors of ratings of executive functions in everyday life, for children both with and without mild TBI.